High Resolution Structural Changes of Schwann Cell and Endothelial Cells in Peripheral Nerves Across Leprosy Spectrum. (April 2014) - Kumar, V.; Sachan, Tarun; Natrajan, Mohan; Sharma, Ankit
ABSTRACT A systematic ultrastructure of peripheral nerves across the spectrum of leprosy was studied with an aim to better understanding the pathogenesis of nerve involvement in leprosy using light and electron microscope. The pathogenesis of nerve destruction varies in leprosy considerably along the spectrum. The study has begun to shed new light on some aspects of the infection of Mycobacterium leprae (M. lepare) and phenomenon has opened new avenue of research and possible mechanism of pathogenesis in TT/BT/BL/LL leprosy. In tuberculoid type (TT) and borderline tuberculoid (BT) leprosy, the degenerative changes of Schwann cells (SCs) and presence of perineural and perivascular cuffing by mononuclear cells. The endoneurial blood vessel (EBV) showed thickening of basement membrane with hypertrophy of EC leading to narrowing or complete occlusion of lumen and causing ischemia. However, borderline lepromatous (BL) and lepromatous leprosy (LL) foamy macrophages and vacuolated SC contain numerous small dense materials, irregular in shape and size was prominent and, considered to be degenerated and fragmented M. Leprae. The dense materials were also found in the cytoplasm of vascular EC. It was revealed that besides SC, the EC of EBV frequently harbor M. leprae in LL. The lumen of the EBV was wide open with enlarged nucleus. In the present study, the ultrastructural characteristics suggest that hypersensitivity mechanisms are possibly responsible for nerve damage in TT/BT leprosy. However, the study indicates that the mechanisms of nerve damage in BL/LL are basically different wherein hypersensitivity appears to play a very limited role.